Introduction of Trichoderma spp. biocontrol strains against Sclerotinia sclerotiorum (Lib.) de Bary change soil microbial community composition in common bean (Phaseolus vulgaris L.) cultivation - de Azevedo Silva, Fábio; de Oliveira Vieira, Vandinelma; Correia da Silva, Rafael [UNESP]; Guariz Pinheiro, Daniel [UNESP]; Antônio Soares, Marcos (Elsevier, 2021)
Biological control represents a promising alternative to maintain the viability and productivity of different agricultural crops. In this work, dry bean (Phaseolus vulgaris L.) was grown in a field contaminated with Sclerotinia sclerotiorum (Lib.) de Bary, the causal agent of white mold disease. We analyzed the impact of the application of antagonistic strains of Trichoderma harzianum ESALQ-1306 and Trichoderma asperellum BRM-29104 on the edaphic native microbiota and endophytic fungal community. The structure of the fungal and bacterial communities was evaluated by next generation sequencing of the 28S and 16S rRNA genes, respectively. The results showed that the introduction of the strains changed the composition of the community without significantly affecting the parameters of abundance and alpha diversity (Anova P > 0.05). Ascomycota (54.8%) and Actinobacteria (37.2%) were predominant in the analyzed communities. Hill's diversity profiles of the treatments were similar in terms of diversity and dominance, being higher in a 90-day period and in the control treatment. NMDS and UPGMA analysis show that treatments of different lengths have low similarity in their composition, however, treatments where Trichoderma spp. were inoculated were relatively similar to the control. T. harzianum ESALQ-1306 promoted a greater quantity of indicator OTUs, 17 in total. T. harzianum ESALQ-1306 and T. asperellum BRM-29104 alter the size (1140 and 449 nodes respectively), connectivity parameters such as average degree (79.28 and 22.29 links respectively) and predominant topological roles in co-occurrence networks, but they do not alter the richness or abundance of orthologous genes. Cultivation time and plant organs were the factors that most influenced the structure of the microbial community. Trichoderma harzianum ESALQ-1306 and T. asperellum BRM-29104 promote the biological control of white mold without deleterious effects on the edaphic and endophytic bean communities.
Keywords: Biocontrol; Metagenomics; Microbial ecology; Non-target